Palincas, N. y Martins, A.C. (eds.) (2024) Gender and Change in Archaeology. European Studies on the Impact of Gender Research on Archaeology and Wider Society. Cham: Springer. ISBN 3031521544. 390 pp. https://link.springer.com/book/10.1007/978-3-031-52155-3 - Sánchez Romero, Margarita (SPAL - Revista de Prehistoria y Arqueología, 2025)
Reseña de la obra: Gender and Change in Archaeology. European Studies on the Impact of Gender Research on Archaeology and Wider Society